Improved recovery stress in multi-walled-carbon-nanotubes reinforced polyurethane. (15th February 2015) - Hashmi, S.A.R.; Prasad, Harish Chandra; Abishera, R.; Bhargaw, Hari Narayan; Naik, Ajay
Graphical abstract: Highlights: Studied recovery stress of CNT reinforced SMTPU under large deformations. New deformations scheme yielded more than 50% improvement in recovery stress. Entire thermo-mechanical programmed cycle of process was performed in liquid medium. Abstract: The shape-recovery performance of multi-walled-carbon-nanotubes (MWCNT) reinforced shape-memory-thermoplastic-polyurethane (SMTPU) was investigated for modified Shape-Memory-Creation-Procedure (SMCP). The modified SMCP replaced the conventional stretching scheme of deformation which is generally employed to attain temporary-shape. A Progressive-Stretch-Relax-Stretch (PSRS) scheme of deformation was introduced to create temporary shape in SMTPU and MWCNT-SMTPU nanocomposites. As compared to the conventional deformation, PSRS deformation exhibited more than 50% increase in the recovery-stress in all the composites. The cast-films of SMTPU having 0, 1, 2, 3 and 5 phr MWCNT were prepared. Significant improvement in recovery-stresses was also observed with the increased content of MWCNT. DSC studies revealed increased glass-transition temperature with MWCNT content. These composites exhibited higher values of shape-fixity with increased content of MWCNT. The samples prepared under PSRS scheme, having 5 phr MWCNT in SMTPU, attained high recovery stress 6.95 MPa as compared to 3.68 MPa with conventional method at 780% strain of the sample.